Manganese nodule and surface sediment compositions: DOMES sites A, B, and C - Piper, David Z; Leong, Kam; Cannon, William F (Supplement to: Piper, DZ et al. (1979): Manganese nodule and surface sediment compositions: domes sites A, B, and C. in: Bischoff, J.L. (ed.), Marine Geology and Oceanography of the Pacific Manganese Nodule Province, Marine Science. Plenum Publishing Corporation, New York, U.S.A., 437-474, https://store.pangaea.de/Projects/NOAA-MMS/chp_10.1007_978-1-4684-3518-4_13.pdf, 1979)
Manganese nodules and associated sediment from the equatorial North Pacific have been examined to ascertain relations between nodule abundance, texture, and composition, and sediment composition, lithology and acoustic stratigraphy. Nodules are most abundant in areas where the uppermost acoustically transparent layer of sediment is less than approximately 15 m thick. Abundance drops off sharply in areas where this acoustic unit is thicker than 20 m. Nodules have average Zn/Mn and Co/Mn ratios which are approximately the same as these ratios for the component of sediment soluble in hydroxylamine hydrochloride-acetic acid. The relations between Cu and Mn and Ni and Mn in the sediment are also approximately the same as in nodules, but only for those nodules which have a smooth surface texture. Granular nodules have relatively more Ni and Cu. Antimony in nodules, similar to Ni, Cu, and Zn, is strongly correlated with Mn, whereas Co, Hf, Th, and U are strongly correlated with Fe. The insoluble component of sediment has a uniform composition which is similar to the composition of terrigenous shale. This similarity holds for the major oxides as well as for Co, Cr, Zn, Hf, Sb, Th, U, Sc, Cs, Rb, and Ta.